Image-guided interstitial brachytherapy for recurrent cervical cancer after radiotherapy: A single institution experience - Ren, Xiaojun; Fu, Yingli; Liu, Zhongshan; Lin, Xia; Qiu, Ling; Li, Yunfeng; Li, Hanyang; Bai, Yuqi; Wang, Tiejun (Frontiers in Oncology, 2022)
Purpose: To evaluate the efficacy and toxicity of image-guided high-dose-rate (HDR) interstitial brachytherapy (ISBT) for the reirradiation of cervical cancer within a previously irradiated area.Methods and Materials: Twenty-three consecutive patients with cervical cancer were re-irradiated with curative intent using brachytherapy (BT)with or without external beam irradiation. The median biologically equivalent dose in 2 Gy fractions (EQD2), for reirradiation was 64.0 Gy (range: 31.3–95.1 Gy), and the median cumulative EQD2 (for primary treatment and reirradiation) was 152.4 Gy (range: 97.8–200.9 Gy). The average clinical target volume was 82.9 cm3 (range: 26.9–208.3 cm3), and the median treatment-free-interval (TFI) was 13 months (range: 3–93 months).Results: The median follow-up time was 19 months (range: 2-59 months). The CR rate after reirradiation was 56.5%. the 1-, 2- 3- and 4-year post-relapse survival (PRS) rate was 65.2%, 43.5%, 33.8%, and 27.1%, respectively. The median re-irradiation EQD2 D2cc of rectum and bladder was 39.5 Gy (range=14.6–96.2 Gy) and 52.1 Gy (range=29.1–114.2 Gy). The median cumulative EQD2 D2cc of rectum and bladder was 115.0 Gy (range=84.4–189.3 Gy) and 130.5 Gy (range=95.5–173.5 Gy). During follow-up, 9(39.1%) patients had experienced grade 3 or 4 late toxicities. Grade ≥3 rectal toxicity occurred in 3 patients (13.0%). Grade ≥3 urinary toxicity occurred in 5 patients (21.7%). One patients (4.3%) had both Grade ≥3 urinary and rectal toxicity. Tumor volume, treatment-free-interval, tumor invasion organ number and local control were significant prognostic factors adversely affecting OS. Conclusions: For recurrent cervical cancer after radiotherapy, reirradiation of HDR-ISBT is feasible, even if the local tumor invasion is large, with a good chance of survival and acceptable side effects.